2002
DOI: 10.1093/emboj/cdf444
|View full text |Cite
|
Sign up to set email alerts
|

Functional cloning of BRF1, a regulator of ARE-dependent mRNA turnover

Abstract: To identify regulators of AU-rich element (ARE)-dependent mRNA turnover we have followed a genetic approach using a mutagenized cell line (slowC) that fails to degrade cytokine mRNA. Accordingly, a GFP reporter construct whose mRNA is under control of the ARE from interleukin-3 gives an increased fluorescence signal in slowC. Here we describe rescue of slowC by a retroviral cDNA library. Flow cytometry allowed us to isolate revertants with reconstituted rapid mRNA decay. The cDNA was identified as butyrate res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
173
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(176 citation statements)
references
References 42 publications
2
173
1
Order By: Relevance
“…This scheme complements a popular displacement model whereby decay-promoting and stability-promoting RBPs are thought to compete for the same binding site (Park et al, 2000;Ming et al, 2001;Stoecklin et al, 2002;Cok et al, 2004). The general association of RBPs to common target RNAs was seen predominantly in the nucleus, but was very reduced in the cytoplasm.…”
Section: Concurrent Binding Of Hur and Auf1 To Common Target Mrnasmentioning
confidence: 73%
See 1 more Smart Citation
“…This scheme complements a popular displacement model whereby decay-promoting and stability-promoting RBPs are thought to compete for the same binding site (Park et al, 2000;Ming et al, 2001;Stoecklin et al, 2002;Cok et al, 2004). The general association of RBPs to common target RNAs was seen predominantly in the nucleus, but was very reduced in the cytoplasm.…”
Section: Concurrent Binding Of Hur and Auf1 To Common Target Mrnasmentioning
confidence: 73%
“…According to a widely established view, HuR/ELAV proteins can compete with AUF1 (Park et al, 2000;Cok et al, 2004) or with other decay-promoting RBPs (Ming et al, 2001;Stoecklin et al, 2002) for binding to the same ARE on specific target mRNAs, but other regulatory schemes have not been formally tested. Moreover, no studies have directly assessed the endogenous association of HuR and AUF1 with target mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…As with classical loss-of-function tumor suppressor genes (Hanahan and Weinberg, 2000;Knudson, 2000), TTP or a closely related gene may be mutated in the tumor cells and transfection restores the missing function. We have sequenced the entire coding region of TTP and BRF1, a structurally related AREbinding zinc-finger protein that also regulates cytokine mRNA turnover (Lai et al, 2000;Stoecklin et al, 2002). In V2D1 tumor cells, no mutation was detected in either gene, and transcripts were of expected size and expressed at the same levels as in parental PB-3c cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of mRNA stabilization is likely to involve ARE-binding proteins as adaptors between the signalling cascade and the decay machinery (Carballo et al, 2001;Mahtani et al, 2001). ARE-binding proteins with assigned functions in vivo include TTP, butyrate response factor-1 (BRF1) and AUF1, all of which promote degradation, as well as HuR that exerts an mRNA stabilizing effect (Carballo et al, 1998;Fan and Steitz, 1998;Peng et al, 1998;Loflin et al, 1999;Lai et al, 2000;Stoecklin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have identified other factors capable of binding AREs with various degrees of avidity. These include selected nuclear ribonucleic proteins (hnRNP A1, hnRNP C (Hamilton et al, 1993), hnRNP D, also known as AUF-1 (Brewer, 1991)), RNA-binding proteins displaying enzymatic activities (GAPDH (Nagy and Rigby, 1995), AUH (Nakagawa et al, 1995)), other HuR-like proteins, belonging to the ELAV family (embryonic lethal abnormal vision) and related to the Drosophila neuron-specific RNA-binding proteins (Hel-N1, HuC, HuD, (Levine et al, 1993;Good, 1995;Ma et al, 1996) and HuR (Fan and Steitz, 1998;Peng et al, 1998), heat shock protein 70 (Hsp70) and others (AUBP (Malter and Hong, 1991), AU-A, AU-B, AU-C (Bohjanen et al, 1991(Bohjanen et al, , 1992, tristetraprolin (Taylor et al, 1996b), butyrate response factor-1 (BRF1), encoding a zinc finger protein homologous to tristetraprolin (Stoecklin et al, 2002), KSRP ), TIA-1 and TIAR (Piecyk et al, 2000)). …”
Section: Are Binding Factorsmentioning
confidence: 99%